Peningkatan Kapasitas Guru Geografi Dalam Pembuatan Peta Digital Berbasis Arc GIS 10.6 di Era. 4.0 - Dahlia, Siti; Putra, Agung Adi; Alwin, Alwin (Uhamka Press, 2019)
One of characteristic geography study is spatial which representation using map. In fact, not all teachers of geography study are able to make of map especially digital map. Nowadays, we live in era 4.0 that is digital and online base. All of teachers geography study should be able to teach students to make maps digitally. Based on it, the aim of Social Service Programme is improve teachers skill for making of digital map using software Arc Gis 10.6. Partner of programme is collaboration with MGMP Geography Kota Depok, with the number of participans ware 16 persons. The method of implementing programme was used workshop, practice with tutorial method, discussion, and evaluation using kahoot aplication and questionnaire. This programme did in Geography Laboratorium which has software Arc Gis 10.6 licensed. The result showed that all of participans attended the training well for indicators: georefernsing, digitasion of polygon, polyline and point, add atribut data, symbology, and layout. Furthermore, based on evaluation programme, the majority teachers gives very good appraisement about facility, speakers and fasilitators, material relevance, and skill enhancement. Based on material evaluation, the majority teachers have difficulty with digitation, symbology, and layout material. The product from this programme was digital map of administrative Jakarta Province.